Conservative Bias : How Jesse Helms Pioneered the Rise of Right-Wing Media and Realigned the Republican Party - Thrift, Bryan Hardin (Sunbelt studies., 2014)
An exploration of how Jesse Helms pioneered the attack on the liberal media while building a new form of southern conservativism, centering on his time as executive vice president of WRAL-TV in Raleigh.